Giant Congenital Melanocytic Nevi in Neonates: Report of Two Cases - Jen-Chung Chien; Dau-Ming Niu; Mao-Shan Wang; Ming-Tzen Liu; Jiing-Feng Lirng; Shu-Jen Chen; Betau Hwang (Elsevier, 2010)
Giant congenital melanocytic nevi are rare, with an estimated incidence of approximately 1 in 20,000 live births. They increase the lifetime risk for malignant melanoma and neurological deficits, including leptomeningeal melanocytosis and epilepsy. Recently, we encountered two patients in whom giant congenital melanocytic nevi were noted at birth. Case 1 presented with the largest nevus spreading across the posterior scalp, neck, chest wall, shoulder and upper back. At the age of 2 months, magnetic resonance imaging (MRI) was performed and no leptomeningeal melanocytosis was found. Case 2 presented with a huge nevus covering most parts of the lower abdomen, lower back, buttocks and bilateral upper thighs. She also had normal MRI findings in the newborn period. At the age of 7 years, leptomeningeal thickening on the surface of the junction between the pons and midbrain was found on brain MRI although she was neurologically asymptomatic. Here, we describe these two cases with congenital melanocytic nevi and review the literature about its clinical manifestations, outcomes, risks for malignant melanoma and neurocutaneous melanosis, and possible surgical interventions.